"I've Been Through It": Assessing Employment Barriers among Unaccompanied Women Experiencing Homelessness. (13th June 2021) - Groton, Danielle; Radey, Melissa
Abstract: Women represent a growing segment of the homeless population; however, little work has examined employment among an important segment of this population: women unaccompanied by children. This study addressed the following research questions: Which common employment barriers (that is, physical health, mental health, substance abuse, or domestic violence) influence employment of unaccompanied women experiencing homelessness? How do these barriers influence the employment experiences of the women? The authors analyzed a cross-sectional sample of unaccompanied women in one community's homeless management information system ( n = 1, 331). Then they completed semistructured interviews ( n = 20) with a subsample of these women. Logistic regression analyses indicated that no employment barrier significantly related to current employment status. Interview data indicated that women perceived physical and mental health issues as barriers to full-time employment. Women reported a struggle to maintain housing even when they had employment. Integrated quantitative and qualitative analyses identified how agency data regarding barriers and employment may miss central barriers (for example, stigma, physical presentation) and employment engagement. Study findings provide support for programs that address housing and current barriers before other employment barriers, the importance of improving federal measures, and recommendations to strengthen agency-level data collection to inform program development and community-based research.